2020
DOI: 10.1083/jcb.202001071
|View full text |Cite
|
Sign up to set email alerts
|

An antibody toolbox to track complex I assembly defines AIF’s mitochondrial function

Abstract: An ability to comprehensively track the assembly intermediates (AIs) of complex I (CI) biogenesis in Drosophila will enable the characterization of the precise mechanism(s) by which various CI regulators modulate CI assembly. Accordingly, we generated 21 novel antibodies to various mitochondrial proteins and used this resource to characterize the mechanism by which apoptosis-inducing factor (AIF) regulates CI biogenesis by tracking the AI profile observed when AIF expression is impaired. We find that when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 35 publications
2
50
0
Order By: Relevance
“…The following mouse antibodies were used for immunoblotting (WB) and/or immunofluorescence (IF) in this study: ATP5A (ab14748, 1:10000 (WB), 1:300 (IF, adult muscle)), Ubiquitin (clone FK2, D058-3, 1:2000 (WB), 1:250 (IF, adult muscle), Actin (MAB1501, 1:1000 (WB)), GAPDH (GTX627408, 1:1000 (WB)). The following rabbit antibodies were used in this study: pS65-Ub (62802S, 1:750 (WB), 1:200 (IF, larval muscle), 1:120 (IF, adult muscle)), COXIV and SDHA (both kind gifts from Edward Owusu-Ansah (Murari et al, 2020), 1:2000 (WB)), Porin (PC548, 1:5000 (WB)). The following secondary antibodies were used: sheep anti-mouse (HRPconjugated, NXA931V, 1:10000 (WB)), donkey anti-rabbit (HRP-conjugated, NA934V, 1:10000 (WB)), goat anti-mouse (AlexaFluor 488, A11001, 1:200 (IF)), goat anti-rabbit (AlexaFluor 594, A11012, 1:200 (IF)), goat anti-rabbit (AlexaFluor 647, A21244, 1:200 (IF)).…”
Section: Antibodies and Dyesmentioning
confidence: 99%
“…The following mouse antibodies were used for immunoblotting (WB) and/or immunofluorescence (IF) in this study: ATP5A (ab14748, 1:10000 (WB), 1:300 (IF, adult muscle)), Ubiquitin (clone FK2, D058-3, 1:2000 (WB), 1:250 (IF, adult muscle), Actin (MAB1501, 1:1000 (WB)), GAPDH (GTX627408, 1:1000 (WB)). The following rabbit antibodies were used in this study: pS65-Ub (62802S, 1:750 (WB), 1:200 (IF, larval muscle), 1:120 (IF, adult muscle)), COXIV and SDHA (both kind gifts from Edward Owusu-Ansah (Murari et al, 2020), 1:2000 (WB)), Porin (PC548, 1:5000 (WB)). The following secondary antibodies were used: sheep anti-mouse (HRPconjugated, NXA931V, 1:10000 (WB)), donkey anti-rabbit (HRP-conjugated, NA934V, 1:10000 (WB)), goat anti-mouse (AlexaFluor 488, A11001, 1:200 (IF)), goat anti-rabbit (AlexaFluor 594, A11012, 1:200 (IF)), goat anti-rabbit (AlexaFluor 647, A21244, 1:200 (IF)).…”
Section: Antibodies and Dyesmentioning
confidence: 99%
“…The level of expression of most of the other CI subunits of the Pp module were reduced in FAF3-kd and FAF4-kd samples to a level on par with the Q and N modules ( Figures 4 L–4N). Because all the subunits in the P D module are very hydrophobic, and perhaps are more refractory to proteolysis than hydrophilic subunits, the P D module is the most stable CI AI in Drosophila thoraces and frequently accumulates when CI biogenesis is stalled at other modules ( Figures 3 H and 3I) ( Murari et al., 2020 ; Garcia et al., 2017 ). Taken together, the subcomplex in profile C most likely corresponds to a stalled AI-T that is undergoing degradation, such that the amounts of the matrix domain modules (Q and N) have decreased, and most subunits in the P P module have been degraded extensively leaving behind NDUFC1 and the relatively more stable P D module subunits.…”
Section: Resultsmentioning
confidence: 99%
“…There are also regulators of CI assembly that have more global effects on OXPHOS assembly. Such is the case for apoptosis-inducing factor, which regulates the intramitochondrial transport of some components of the mitochondrial contact site and cristae organizing system, thereby influencing CI assembly indirectly ( Murari et al., 2020 ). A thorough characterization of the roles of all CIAFs is required as it will improve our understanding of CI assembly, and possibly, uncover new therapeutic options for mitochondrial CI diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, loss of AIF has been shown to result in loss of ETC complex I (CI) levels and activity [ 65–68 ], although it seems that its role in CI biogenesis is limited to its facilitation of CHCHD4 import, since overexpression of CHCHD4 or import of CHCHD4 independent of AIF has been shown to render AIF dispensable for CI biogenesis [ 17 , 69 ]. A recent study in Drosophila suggests that compromised import of the Mia40 substrate MIC19 (a component of the mitochondrial contact site and cristae organising system) in the context of loss of Drosophila AIF (dAIF) is an underlying mechanism for dAIF affecting CI biogenesis [ 70 ].…”
Section: Chchd4 In Humansmentioning
confidence: 99%
“…TIMM9, TIMM10). Additionally, a number of CHCHD4 substrates function in the regulation of mitochondrial ultrastructure, including the formation of mitochondrial cristae and the organisation of the IMM [ 70 , 78 ]. Interestingly, a study in zebrafish demonstrated that homozygous loss of chchd4a , the essential homologue of CHCHD4 , resulted in enlarged mitochondrial structures, and reduced basal oxygen consumption rate (OCR) in chchd4a targeted zebrafish embryos [ 18 ].…”
Section: Chchd4 (Mia40) Substrates and Mitochondrial Functionmentioning
confidence: 99%